Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Pajak, Dan Profitabilitas Terhadap Kebijakan Hutang Studi Kasus Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2018 - Setyo Wahyudi; Jeni Susyanti; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2021)
Abstract A company was founded with the aim of achieving maximum profits. With large profits, the company can grow and continue to grow. In a company there is a manager who manages the company and has the power to make decisions and determine policies for the company. One important policy in the company is the funding policy. This policy is related to meeting needs, determining the amount of capital to be managed and how to use it. In determining funding, managers often carry out a debt policy to increase company funds. In this study the authors used the Explanatory Research method with a quantitative approach. The population and sample in this study are pharmaceutical companies listed on the IDX. In analyzing the data the researchers used multiplen linear regression. The results showed that managerial ownership and profitability had a significant effect on debt policy, while institutional ownership and tax had no significant effect on debt policy. Keywords :Managerial Ownership, Institusional Ownership, Tax, Profitability, Debt Policy